The Impact of Type Script Cooperative Learning of the Mutual Cooperation Behavior on Economic Subjects - Wahyudin, M; Maryani, L; Aryanto Sopiansah, V (KnE Social Sciences, 2018)
This study purposes to know the impact of type script cooperative learning of the mutual cooperation behavior on economic subject. Respondents from two classes were selected randomly at the west java provincial school in the country of Indonesia. The study used a pre-test-post-test control group design that was used to compare the impact of cooperative type script and cooperative learning approaches commonly used by teachers in general to know three aspects of mutual cooperation or Gotong Royong (care, tolerance and contribution). The study found significant results in the type script cooperative learning model in improving the behavior of mutual cooperation (care, tolerance and contribution). Keywords: type script cooperative learning model, the mutual cooperation behavior or Gotong Royong (care, tolerance and contribution), economic subject.